2023
DOI: 10.5194/nhess-23-231-2023
|View full text |Cite
|
Sign up to set email alerts
|

Scrutinizing and rooting the multiple anomalies of Nepal earthquake sequence in 2015 with the deviation–time–space criterion and homologous lithosphere–coversphere–atmosphere–ionosphere coupling physics

Abstract: Abstract. The continuous increasing of Earth observations benefits geosciences and seismicity study but increases greatly the difficulties in understanding and discriminating multiple source data. Although the lithosphere–coversphere–atmosphere-ionosphere (LCAI) coupling paradigm and the deviation–time–space (DTS) criterion were presented for better searching for and understanding the potential seismic anomalies from multiple observations, the strict consistency of spatiotemporal characteristics and homologous… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 90 publications
0
18
0
Order By: Relevance
“…Politis et al [2021] present a comprehensive analysis of VLF radio signal anomalies separately during the same EQ. Hayakawa et al [ , 2022, Chetia [2020], Marchetti et al [2019], Ouzounov et al [2021], Wu et al [2023] and Zang et al [2023] reported a similar extensive study for EQs in Japan, Italy, Nepal and China including more parameters like ULF/ELF emissions, VLF anomaly, air temperature, etc. that mostly corroborates the previous findings.…”
Section: Introductionmentioning
confidence: 81%
“…Politis et al [2021] present a comprehensive analysis of VLF radio signal anomalies separately during the same EQ. Hayakawa et al [ , 2022, Chetia [2020], Marchetti et al [2019], Ouzounov et al [2021], Wu et al [2023] and Zang et al [2023] reported a similar extensive study for EQs in Japan, Italy, Nepal and China including more parameters like ULF/ELF emissions, VLF anomaly, air temperature, etc. that mostly corroborates the previous findings.…”
Section: Introductionmentioning
confidence: 81%
“…Computational methods have been applied by different researchers to study the phenomena of earthquake generation and for its prediction. Machine learning (ML) has emerged as very promising domain that offers multiple methods that can be applied on datasets for prediction of outcomes [45]. Researchers have processed earthquake datasets of different regions using ML methods .…”
Section: Computational Approachesmentioning
confidence: 99%
“…Previous works identified an important feature: the spatial organisation of the anomalies before the earthquake [69,110], identifying a pattern that started far from the epicentre and gradually approached the incoming earthquake. However, in this work, only some considerations about the seismic patterns of Figure 1 can be discussed, as the anomalies in the atmosphere and ionosphere have been extracted in areas closer to the epicentre than the entire Dobrovolsky area.…”
Section: Figure 18mentioning
confidence: 99%